Sensory phenomena in children with Tourette syndrome or autism spectrum disorder - Prato, Adriana; Saia, Federica; Ferrigno, Marianna; Finocchiaro, Valentina; Barone, Rita; Rizzo, Renata (Frontiers in Psychiatry, 2024)
Background Tourette syndrome (TS) and autism spectrum disorder (ASD) are two neurodevelopmental disorders with an onset before the age of 18 years. TS patients frequently reported atypical sensory phenomena (SP). Sensory processing abnormalities are also particularly frequent in ASD individuals. Objectives Considering the higher rate of atypical sensory behaviours in both neurodevelopmental disorders, in the present study we analysed sensory experiences in patients with ASD and in patients with TS. Methods We enrolled patients with a primary diagnosis of TS or ASD. All participants were assessed for primary diagnosis and associated comorbidities. The presence of sensory behaviours was investigated using the University of Sao Paulo’s Sensory Phenomena Scale (USP-SPS). Results SP were significantly more represented in the ASD-group versus TS-group, except for sound just-right perceptions and energy to released. ASD participants presented higher mean scores in all fields of USP-SPS severity scale respect on TS patients and healthy controls. The USP-SPS total score had significant positive correlations with the CYBOCS and MASC total scores in the TS cohort. In the ASD group, the USP-SPS total score was significantly negative correlated with the total IQ and marginally positive correlated with ADOS total score. Conclusion SP are a frequently reported characteristic both of ASD and TS. Future studies are needed to better evaluate the differences on their phenomenology in patients with TS and ASD.